Proceedings of the International Conference on Aerospace System Science and Engineering 2019 - Jing, Zhongliang; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book presents the proceedings of the International Conference on Aerospace System Science and Engineering (ICASSE 2019), held in Toronto, Canada, on July 30-August 1, 2019, and jointly organized by the University of Toronto Institute for Aerospace Studies (UTIAS) and the Shanghai Jiao Tong University School of Aeronautics and Astronautics. ICASSE 2019 provided a forum that brought together experts on aeronautics and astronautics to share new ideas and findings. These proceedings present high-quality contributions in the areas of aerospace system science and engineering, including topics such as trans-space vehicle system design and integration, air vehicle systems, space vehicle systems, near-space vehicle systems, aerospace robotics and unmanned systems, communication, navigation and surveillance, aerodynamics and aircraft design, dynamics and control, aerospace propulsion, avionics systems, optoelectronic systems, and air traffic management.
Trans-space vehicle systems design and integration -- Air vehicle systems -- Space vehicle systems -- Near-space vehicle systems -- Aerospace robotics and unmanned system -- Communication, navigation and surveillance -- Aerodynamics and aircraft design -- Dynamics and control -- Aerospace propulsion -- Avionics system -- Opto-electronic system -- Air traffic management -- Earth observation -- Deep space exploration -- Bionic micro-aircraft/spacecraft -- Intelligent sensing and Information fusion.
Keywords: Space sciences; Aerospace engineering; Astronautics; Control engineering; Vibration; Dynamical systems; Dynamics; Engineering design; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Aerospace Technology and Astronautics; Control and Systems Theory; Vibration, Dynamical Systems, Control; Engineering Design